Computer Prediction of Adsorption Water Purification Process in Rapid Cone-Shaped Filters - Bomba, Andrii; Klymyuk, Yurii; Prysіazhnіuk, Igor (Моделювання, керування та інформаційні технології, 2019)
In the paper a mathematical model for computer predicting the process of adsorption purification of water from impurities in rapid filters taking into account changes in the temperature of the filtration flow along the height of the filter while observing the constant filtration rate is formulated. An algorithm for numerically-asymptotic approximation of solution of the corresponding nonlinear singularly perturbed boundary value problem for a model region of a conical shape, bounded two equipotential surfaces and a surface flow, is developed. The proposed model allows through computer experiments to investigate changes in the characteristics of porous loads (filtration coefficients, active porosity), to predict the optimal variants for using adsorbents, and increasing the duration of the filters operation due to the choice of their shape, taking into account the effect on the process of adsorption purification of water not only changes in the filtration rate flow along the height of the filter, but also the temperature.